Becoming Apostolic : Conversations with Older Roman Catholic Sisters - Sexton, Catherine (Brill's Studies in Catholic Theology, 2024)
This book explores the experience and understanding of Roman Catholic sisters of their vocation to the apostolic form of religious life as they age.Based on interviews with twelve religious women, it draws on the practice of Lectio Divina to exp